Clamped Carotid Dissection Can Reduce Postoperative Stroke After Carotid Endarterectomy. (February 2022) - Pini, Rodolfo; Faggioli, Gianluca; Palermo, Sergio; Fronterrè, Sara; Alaidroos, Moad; Vacirca, Andrea; Gallitto, Enrico; Gargiulo, Mauro
Background: The outcomes of carotid endarterectomy (CEA) are constantly reported in a multitude of studies; however, the specific causes of perioperative stroke have been scarcely investigated. The aim of the present study was to analyze and categorize the causes of perioperative strokes after CEA.Methods: All CEAs performed from 2006 to 2019 in a single center were collected. CEA was routinely performed under general anesthesia, with routine shunting and patching, using cerebral near-infrared spectroscopy monitoring. Carotid exposure technique was classified as either clamped-dissection (CD) or preclamping-dissection (PCD) if the carotid bifurcation was dissected after or prior to carotid clamping. Perioperative and 30-day strokes and their possible mechanisms were evaluated according to preoperative symptoms and surgical technique adopted.Results: Among 1760 CEAs performed, 30 (1.7%) perioperative strokes occurred. 14 (47%) were identified upon emergence from general anesthesia, and 16 (53%) were noted in the first 30 days following intervention. Stroke etiology was categorized as follows: technical (acute thrombosis or intimal flap or due to intraoperative complications), embolic (no recognized technical defect), hemorrhagic, or contralateral. Symptomatic patients had a significantly higher rate of any type of stroke than asymptomatic patients (3.8% vs 0.9%, P = .0001). CD was protective for postoperative stroke (0.9% vs 3.1%, P = .001) in both symptomatic and asymptomatic patients (2.5% vs 5.9%, P = .05; 0.4% vs 1.9%, P = .005), particularly for the cohort in which symptomatic patients (0.7% vs 3.2%, P = .04) suffered postoperative embolic stroke.Conclusion: Perioperative stroke in CEA may be multifactorial in etiology, including a result of technical errors. A CD technique may help reduce the incidence of perioperative stroke.